Forensic Anthropology in biological profiling of human skeletal remains (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
The anthropological analysis for biological profiling of the skeletal material from forensic context is of paramount importance and forms a basic step in forensic anthropology. Forensic anthropology is an applied discipline of anthropology wherein standard scientific methods and techniques developed in skeletal biology, osteology and physical anthropology are applied for medico legal purpose. It forms an integral part of identification process as it allows relatively fast and accurate data that could narrow down the investigators search field. Traditional anthropological assessment of biological identity remains an essential component in the process, serving to limit misidentification and provide additional information upon which to base and support positive identification
Keywords: Forensic anthropology; anthropological analysis